From the margins: Security, crime, and prison confinement - Frois, C. (Conflict and Society: Advances in Research, 2024)
How does our understanding of security change when we reflect on it from the perspective of crime offender, and within the space where the security apparatus assumes a vital importance—the prison? Based on ethnographic data from 12 prison facilities in Portugal, in this article I discuss vernacular notions of security from the perspective of male and female inmates. My aim is to bring to the forefront of the Anthropology of Security research the experiences, practices, and discourses of actors that so far have been excluded from the crime-security nexus debate.